The utility of biomarker excretion rates in acute kidney injury - Md Ralib, Azrina; Pickering, John W.; Devarajah, Prasad; Endre, Zoltan H. (2011)
INTRODUCTION: The concentration of urinary biomarkers of acute kidney injury (AKI) is influenced by variation in urinary concentration within and between individuals.1 Normalisation to urine creatinine concentration is commonly used to account for this variation.2 The accuracy of this method is compromised by tubular secretion of creatinine, and variations in urine creatinine excretion in non-steady state when glomerular filtration rate (GFR) changes.1 Alternatives to normalisation to creatinine include using the absolute biomarker concentration or quantifying the biomarker excretion rate. Intuitively, the excretion rate may also account for variation in water reabsorption and urine flow rate. In addition, total biomarker excretion in AKI might more accurately reflect the mass of injured tubular cells, a function of both severity and duration, parameters associated with long-term mortality.3